Liner shipping markets, networks and strategies: The implications for port development on the West Coast of South America - Gordon Wilmsmeier (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
This paper, predominantly on the challenges for port development, in some important sense cannot help but also be about the deeper phenomena of structural change in the maritime industry and geographical shift. The main objective is to analyse the evolution of symptoms of change in the liner shipping industry within South America and more particularly on the West Coast, as these changes are direct drivers for port infrastructure and port system development, which is both economically interesting and a matter of serious policy significance in its own right. Port infrastructure and the quality of shipping services in a region or country are important determinants for the countries integration in the global market and the competitiveness of the same. Given the sustained growth in emerging economies, despite the recent crisis, port infrastructure development has emerged as a crucial issue for future economic growth. The West Coast of South America (WCSA) and particularly Chile have been experiencing significant economic expansion over the last two decades. However, the role of infrastructure and its contribution to continued economic and social development has only recently returned to the political agendas.
Keywords: 330